Synthesis and physical-chemical properties of 3-(4-(tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazol-4-amines - I. I. Aksyonova; O. I. Panasenko; Ye. G. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. 1,2,4-triazole derivatives are widely used in medical practice due to its wide range of biological effect and small toxicity. This fact makes this class of organic heterocyclic compounds especially interesting and promising for the study of their physical-chemical and biological properties. Thirteen novel compounds, namely 3-(4- (tert-butyl)phenyl)-5-(R-ylthio)-4H-1,2,4-triazole-4-amines, that were not previously described in the literature, have been synthesized with the aim of search for new potentially biologically active compounds.